Tillståndsprövningens gränser - Deldomar och rättssäkerheten i miljömål - Stensson,Julia (2024)
The paper examines the conditions for issuing partial judgments during the permit process in environmental cases and how this relates to the principle of legality and legal certainty. Partial judgments may speed up the start of envi-ronmentally hazardous activities. However, the partial judgment process is not specifically prescribed in the Environmental Code; the area is mainly practice-driven. The paper uses a legal-dogmatic method to analyze current law based on statutory text, case law, preparatory works and doctrine. The partial judg-ment process can offer a solution to some of the problems posed by lengthy licensing procedures, but legal safeguards such as the legal force of judg-ments, the principle of publicity and the possibility of appeal are central to maintaining confidence in public power. For example, partial judgements can-not be used to try issues that can be reopened later, and a robust environmen-tal impact assessment is a prerequisite for obtaining an interim permit. Case law shows that on a few occasions the Swedish Land and Environment Court of Appeal has set aside partial judgments due to procedural deficiencies, which signals that there is uncertainty about how the process should be han-dled in practice. From a due process perspective, the paper highlights, among other things, the importance of transparency and publicity in the proceedings. At the same time, the paper emphasizes that partial judgments, if used correct-ly, can help to address certain legal certainty problems caused by long pro-cessing times. However, the principle of legality is challenged by the fact that the partial judgment process in the granting of permits for environmentally hazardous activities has no specific provision in law, a risk has been ex-pressed for divergent practice formation and reduced predictability. In sum-mary, the paper identifies a number of different prerequisites for granting par-tial judgment in environmental cases. Furthermore, the paper highlights the need for further research to clarify the legal situation and to ensure that partial judgments are used in a legally secure and effective manner. It concludes that partial judgments can be an effective tool to speed up the commencement of proceedings, but that certain procedural conditions are required to ensure legal certainty.
Keywords: Miljörätt; miljöprocessrätt; rättssäkerhet; legalitetsprincipen